2009
DOI: 10.1037/a0017840
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic variability in the dopamine receptor D2 in relation to behavioral inhibition and impulsivity/sensation seeking: An exploratory study with d-amphetamine in healthy participants.

Abstract: The dopamine D2 receptor (DRD2) appears to be involved in impulsive behaviors, and particularly in behavioral inhibition. We sought to determine whether inhibition and impulsivity were related to genetic polymorphisms in the DRD2 gene (DRD2) in healthy volunteers (N = 93). Participants received placebo or d-amphetamine in random order. They performed the stop task, measuring behavioral inhibition, and rated their mood states on each session. They also completed the Zuckerman-Kuhlman Personality Questionnaire, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 66 publications
5
87
0
Order By: Relevance
“…Because epidemiological studies indicate that sensitivity to drug liking in humans can predict an individual's susceptibility to drug abuse (Haertzen et al, 1983;Schuckit, 2009), drug sensitivity and abuse are hypothesized to share a genetic basis. This hypothesis is supported by genetic association studies in humans that have identified genes that influence both acute sensitivity (Hamidovic et al, 2009(Hamidovic et al, , 2010Lott et al, 2005Lott et al, , 2006Dlugos et al, 2011) and dependence (Ho et al, 2010).…”
Section: Introductionsupporting
confidence: 58%
“…Because epidemiological studies indicate that sensitivity to drug liking in humans can predict an individual's susceptibility to drug abuse (Haertzen et al, 1983;Schuckit, 2009), drug sensitivity and abuse are hypothesized to share a genetic basis. This hypothesis is supported by genetic association studies in humans that have identified genes that influence both acute sensitivity (Hamidovic et al, 2009(Hamidovic et al, , 2010Lott et al, 2005Lott et al, , 2006Dlugos et al, 2011) and dependence (Ho et al, 2010).…”
Section: Introductionsupporting
confidence: 58%
“…For instance, we did not explore the moderating role of participant age, level of education, waiting time between drug administration and testing, length of testing session, or time of day. Moderators of great interest, which might be expected to affect results based on previous studies but which could not be assessed because of insufficient available data, include individuals' baseline cognitive ability and individuals' variants of dopamine-related genes such as COMT and DRD2 (see Hamidovic et al, 2009;Mattay et al, 2003; but see also Wardle, Hart, Palmer, & de Wit, 2013, for null results). Consistent with the nonmonotonic relation between dopamine activity and performance, there is evidence that stimulants can impair performance in normal individuals who are especially high performing (Farah, Haimm, Sankoorikal, & Chatterjee, 2009;De Wit et al, 2002;De Wit, Crean, & Richards, 2000;Mattay et al, 2000).…”
Section: Summary and Interpretation Of Resultsmentioning
confidence: 99%
“…Correlations were obtained from Ilieva, Boland, and Farah (2013; Flanker, Go/No-Go, n-back, Digit Span Backward and Forward, delayed memory for words and faces; 46 participants); Mintzer and Griffiths (2007; n-back, Sternberg memory task, delayed memory for words; 18 participants); and Hamidovic, Dlugos, Skol, Palmer, and de Wit (2009), combined with a set of unpublished data from Dr. Harriet de Wit's laboratory (Stop Signal task, 299 participants). When correlations for a given task (e.g., n-back) were available from more than one data set, we estimated a composite through meta-analyzing the available correlations based on a random effects model.…”
Section: Notesmentioning
confidence: 99%
“…As well, anxious individuals appear to be hypersensitive to negative consequences following their actions and are risk-averse (Maner & Schmidt, 2006;Meyer-Lindenberg, 2010;Mitte, 2008;Raghunathan & Pham, 1999). Perhaps surprisingly, these personality traits have all been associated with individual differences in dopamine expression (Hamidovic, Dlugos, Skol, Palmer, & de Wit, 2009;Laine, Ahonen, Rasanen, & Tiihonen, 2001;Lawford, Young, Noble, Kann, & Ritchie, 2006;Montag et al, 2008), reinforcement sensitivity (Maner & Schmidt, 2006), and/or vulnerability to addiction (Conrod & Woicik, 2002). Hence in the present study we utilized the PST to elucidate individual differences in decision making related to personality.…”
Section: Personalitymentioning
confidence: 99%